(untitled) (Advances in Military Technology, 2019)
The article deals with the pressing process of the samples from bismuth powder, which were used in place of the bullet in order to optimize the frangible bullets manufacturing process. Cylindrical samples with a diameter of 9 mm were compacted by cold pressing in a cylindrical rigid die without sintering. Various pressing conditions (the changing of pressing force, pressing velocity and dwell time) were applied for compacting the samples. After compaction, the axial strength of the samples was tested to determine the optimal manufacturing process of the frangible bullet based on the bismuth powders.